2013
DOI: 10.5194/acp-13-10227-2013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CO, C<sub>2</sub>H<sub>6</sub> and aerosols in a boreal fire plume over eastern Canada during BORTAS 2011 using ground- and satellite-based observations and model simulations

Abstract: Abstract. We present the results of total column measurements of CO, C2H6 and fine-mode aerosol optical depth (AOD) during the "Quantifying the impact of BOReal forest fires on Tropospheric oxidants over the Atlantic using Aircraft and Satellites" (BORTAS-B) campaign over eastern Canada. Ground-based observations, using Fourier transform spectrometers (FTSs) and sun photometers, were carried out in July and August 2011. These measurements were taken in Halifax, Nova Scotia, which is an ideal location to monito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 45 publications
7
26
0
Order By: Relevance
“…CO concentrations of up to 800 ppb were observed between 5000-8000 m, whereas OA did not exceed 30 µg m −3 . This disparity is attributed to the removal of OA from plumes encountered during flight B622 (20 July) by precipitation prior to sampling following advection through clouds, as corroborated by meteorological observations and back trajectory models (Griffin et al, 2013;Taylor et al, 2014). Wet deposition of aerosol reduced OA to background levels, while CO concentrations remained elevated to similar levels as observed at lower altitudes.…”
Section: Spatial and Temporal Variability In Bb Emissions Propertiesmentioning
confidence: 68%
“…CO concentrations of up to 800 ppb were observed between 5000-8000 m, whereas OA did not exceed 30 µg m −3 . This disparity is attributed to the removal of OA from plumes encountered during flight B622 (20 July) by precipitation prior to sampling following advection through clouds, as corroborated by meteorological observations and back trajectory models (Griffin et al, 2013;Taylor et al, 2014). Wet deposition of aerosol reduced OA to background levels, while CO concentrations remained elevated to similar levels as observed at lower altitudes.…”
Section: Spatial and Temporal Variability In Bb Emissions Propertiesmentioning
confidence: 68%
“…As demonstrated in Fig. 7 of Griffin et al (2013), the finemode AOD is generally positively correlated with total column CO throughout the campaign. However, not all measurements of specific air masses follow this trend, and it is one of these exceptions that is investigated in this paper.…”
Section: Dalhousie Ground Station Observationsmentioning
confidence: 75%
“…Uncertainties in the derived columns were calculated in a manner similar to that described by Batchelor et al (2009) and Griffin et al (2013). Errors considered in our calculations include the smoothing error, measurement error, uncertainties in the HITRAN 2008 line parameters, and errors in the temperature profile.…”
Section: Trace Gas Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main mission of IASI is operational meteorology (e.g., Zhou et al, 2009), although air-composition and climate applications are also well covered by the instrument as also discussed before launch (e.g., Chazette et al, 1998;Clerbaux et al, 1998) and now demonstrated (e.g., Crevoisier et al, 2013a;Griffin et al, 2013;Grieco et al, 2013). Hereafter we will only discuss the comparison between IASIderived WVMR and the simultaneous measurements performed by a H 2 O-Raman lidar deployed on the Balearic island of Menorca in the framework of the Hydrological cycle in the Mediterranean eXperiment (HyMeX, http: //www.hymex.org/, Chazette et al, 2014) and ChemistryAerosol Mediterranean Experiment (ChArMEx, http://www.…”
Section: P Chazette Et Al: Comparison Of Iasi Water Vapor Retrievalmentioning
confidence: 99%